Analysis Of Market Reaction to The 2024 Presidential Election Results Announcement on Energy Sector Companies Listed on The IDX - Tiffani, Ignasia; Powell, Karen Arecia; Dewi, Vera Intanie (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
Political events are one of the events that can affect stock prices because these events are related to the stability of the country's economy. The political event that wants to be tested for its information content on the capital market in Indonesia is the announcement of the 2024 presidential election results. Investor reaction can be measured through two variables, namely abnormal return and trading volume activity. This study aims to determine the reaction of the capital market in Indonesia to the announcement of the 2024 election results on the capital market with an event study approach. This study uses a comparative study method and a market model approach in calculating expected returns. The research period is an estimation period of 17 days and an observation period of 11 days. The sample determination used purposive sampling technique and examined 78 issuers from 86 energy sector issuers listed on the IDX. The results showed no difference in abnormal returns and trading volume activity in the period before and after the announcement of election results. In terms of abnormal returns, it shows that the announcement of election results does not contain information that can cause the market to react. Meanwhile, in terms of trading volume activity, investors tend to focus on long-term analysis related to the policies of the new government so as not to make hasty decisions in investing.